PENGARUH KOMPETENSI MAHASISWA, PROGRAM MAGANG, CAREER ADAPTABILITY TERHADAP KESIAPAN KERJA MAHASISWA STIE TAMANSISWA BANJARNEGARA TAHUN 2024 - lusaputra, fadhil ghani; Lustono, Lustono; Hayati, Sri; Suryani, Ratna (Medikonis, 2025)
ABSTRACT In the era of globalization and digitalization in the workforce, the high rate of open unemployment indicates low job readiness, particularly among final-year students entering the workforce. Non-degree learning programs organized by organizations or industries provide knowledge and skills with high relevance to the workforce and business sectors. These are offered through short courses, boot camps, massive open online courses (MOOCs), and other formats, followed by collaborative activities with fellow participants or partner organization personnel in projects or case studies. However, due to the limited prior research discussing this topic, this study aims to examine the influence of student competencies, internship programs, and career adaptability on the job readiness of final-year students in the digital era. A total of 210 students participated using quota sampling to fill out questionnaires based on primary data sources. A purposive sampling method was applied with the criterion that participants had prior internship experience. Regression analysis results show that, partially, student competencies, internship programs, and career adaptability have a significant effect on job readiness. The participative level of these research variables contributes 70.5% to the job readiness of students. This indicates that graduate competencies (students), internship programs, and career adaptability are essential factors that students must possess to enhance job readiness. Students with career adaptability are concerned about their future careers, making them more prepared to face changes in the workplace in the context of global competition and digitalization.